Environmental Kuznets Curves for carbon emissions: A critical survey - Nektarios Aslanidis (Fondazione Eni Enrico Mattei (FEEM), 2009)
The empirical finding of an inverse U-shaped relationship between per capita income and pollution, the so-called Environmental Kuznets Curve (EKC), suggests that as countries experience economic growth, environmental deterioration decelerates and thus becomes less of an issue. Focusing on the prime example of carbon emissions, the present article provides a critical review of the new econometric techniques that have questioned the baseline polynomial specification in the EKC literature. We discuss issues related to the functional form, heterogeneity, spurious regressions and spatial dependence to address whether and to what extent the EKC can be observed. Despite these new approaches, there is still no clear-cut evidence supporting the existence of the EKC for carbon emissions.
Keywords: C20; Q32; Q50; O13; 330; Environmental Kuznets Curve; Carbon Emissions; Functional Form; Heterogeneity; Spurious Regressions; Spatial Dependence